"I had to try all the things that I could:" A Qualitative Study of Breastfeeding Mothers' Experience With Trying to Increase Their Milk Supply. (14th June 2022) - Ryan, Rachel; Bihuniak, Jessica; Hepworth, Alllison; Lyndon, Audrey
Abstract: Objectives: Perceived insufficient milk is a primary contributor to early breastfeeding cessation worldwide. Breastfeeding mothers may consume specific foods, beverages, and herbal supplements, or use behavioral strategies to boost milk production, however, research on this topic is limited, especially in the United States (US). The purpose of this study was to qualitatively describe US breastfeeding mothers' experiences with trying to increase their milk supply. Methods: Breastfeeding mothers of infants ages birth to 24 months in the US who reported current or previous use of foods, beverages, or herbal supplements to increase milk supply were purposefully sampled from a larger cross-sectional survey study. Individual interviews were conducted by phone with each participant using a semi-structured interview guide. The interviews were transcribed verbatim and analyzed using reflexive thematic analysis. Results: Participants (N = 19) identified with diverse racial and ethnic identities, had a range of educational experiences, residential community types (i.e., urban, rural, suburban), WIC participation, and infant ages. Most had prior breastfeeding experience. Mothers expressed determination and commitment to breastfeeding but struggled to breastfeed and increase their milk supply. Therefore, they sought information and support from multiple sources. Mothers used individualized approaches to address milk supply concerns, while taking into consideration factors such as recommendations from others, and the convenience, taste, cost, and perceived safety of potential galactagogues. At the time of the interview, most mothers had resolved their breastfeeding problems or came to accept their breastfeeding journey. Conclusions: Results highlight numerous opportunities for lactation support professionals to address perceived insufficient milk and to guide breastfeeding parents toward safe and effective strategies for increasing breast milk production. Funding Sources: None.